Formation mechanism of polyaniline self‐assembled needles and urchin‐like structures assisted by magnesium oxide. Issue 4 (27th October 2014) - Ibrahim, Michael; Bassil, Maria; Khoury, Tony; Demirci, Umit B; El Tahchi, Mario; Miele, Philippe
<x xml:space="preserve">Abstract</x> Chemical oxidative polymerization, in the presence of MgO particles, was used to synthesize, for the first time, polyaniline needles and urchin‐like structures. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>